Battery-like flexible supercapacitors from vertical 3D diamond/graphite composite films on carbon cloth. (September 2022) - Long, Junjie; Guan, Lei; Wang, Jian; Liu, Huiqiang; Wang, Bing; Xiong, Ying
Abstract: Flexible supercapacitors (SCs) based on carbon nanomaterials are one of the promising energy storage devices for wearable electron devices. However, their low energy density and cycle stability severely restrict further practical applications. The development of unique capacitor electrodes is expected largely to overcome these challenges. Herein, vertical 3D diamond/graphite (DG) composite films are directly grown on carbon cloth (CC) using a microwave plasma chemical vapor deposition (MPCVD) technique. Thin, straight nanosheets, consisted of diamond as core and graphite as shell, are interlaced with each other to form a 3D porous structure. As a binder- and additive-free electrode material, the DG/CC electrodes are used to construct electrical double layer capacitors (EDLCs) in diluted H2 SO4 solution and pseudocapacitors (PCs) using Fe(CN)6 3−/4- redox electrolytes. Both EDLCs and PCs exhibit large specific capacitance and high capacitance retention. When assembled as all-solid-state flexible symmetric SCs, they offer high full-cell capacitances of 30.4 and 143.6 mF cm −2 at 10 mV s −1 for EDLCs and PCs, respectively. The power densities are 6.3 μW cm −2 and 3.0 mW cm −2 for EDLCs and PCs, together with their energy densities of 3.7 and 86.2 μWh cm −2, respectively. As flexible SCs, the specific capacitance can be completely recovered for EDLCs and has only about 6.7% loss for PCs even after the U-shape bending state. Such vertical 3D porous DG films are thus promising for the construction of high-performance battery-like SCs for an intelligent wearable energy supplier. Graphical abstract: Image 1 Highlights: Vertical 3D diamond/graphene composite films were synthesized on carbon cloth to construct battery-like flexible SCs. In-situ electrochemical anodic polarization treatment remarkably enhanced the electrochemical performance. High energy densities with large power densities were obtained in the battery-like SCs.